MENINGKATKAN HASIL BELAJAR MELALUI MODEL PEMBELAJARAN STUDENT FACILITATOR AND EXPLAINING PELAJARAN IPA KELAS V SD NEGERI 1 LAPARA KABUPATEN BUTON SELATAN - Widiarti, Risna (TAKSONOMI: Jurnal Penelitian Pendidikan Dasar, 2021)
This study aims to improve learning outcomes throughv the Student Facilitator and Explaining Learning Model for Class V Science Lessons at SDNegeri I Lapara, South Buton Regency. The design and model used in this research is the Kemmis and Taggart model which includes planning, implementation, observation, reflection and re-planning and the type of research conducted by the. Researcher is classroom action research (CAR). The subjects of this study were all 12th graders of SD Negeri 1 Lapara consisting of 6 boys and 6 girls in the 2021/2022 academic year. From the results of the evaluation of the first cycle, data was obtained from 12 students there were student who scored ≥75 or Classically reached 58.33% with an average value of 75.83 and the weight of thescore achieved was 910, while in the.second cycle classically the learning outcomes students increased by 25% where from 12.students, there were 10 students who scored ≥75 or classically reached 83.33% with an average value of 90.83 and a weighted score achieved as much as 1,090. Based on the results of the study, it was concluded that the application of the Student Facilitator and Explaining learning model could improve student learning outcomes in science lessons in class V SD Negeri I Lapara, South ButonRegency